Scaling trends of on-chip power distribution noise. - Mezhiba, A.V (IEEE Transactions on VLSI systems)
The design of power distribution networks in high-performance integrated circuits has become significantly more challenging with recent advances in process technologies. As on-chip currents exceed tens of amperes and circuit clock periods are reduced well below a nanosecond, the signal integrity of on-chip power supply has become a primary concern in the integrated circuit design. The scaling behavior of the inductive and resistance voltage drops across the on-chip power distribution networks is the subject of this paper. The existing work on power distribution noise scaling is reviewed and extended to include the scaling behavior of the inductance of the on-chip global power distribution networks in high-performance flip-chip packaged integrated circuits. As the dimensions of the on-chip devices are scaled by S, where S>1, the resistive voltage drop across the power grids remains constant and the inductive voltage drop increases by S, if the metal thickness is maintained constant. Consequently, the signal-to-noise ratio decreases by S in the case of resistive noise and by S2 in the case of inductive noise. As compared to the constant metal thickness scenario, ideal interconnect scaling of the global power grid mitigates the unfavorable scaling of the inductive noise but exacerbates the scaling of resistive noise by a factor of S. On-chip inductive noise will, therefore, become of greater significance with technology scaling. Careful tradeoffs between the resistance and inductance of the power distribution networks will be necessary in nanometer technologies to achieve minimum power supply noise.